2019
DOI: 10.48550/arxiv.1911.12597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lidar-Camera Co-Training for Semi-Supervised Road Detection

Luca Caltagirone,
Lennart Svensson,
Mattias Wahde
et al.

Abstract: Recent advances in the field of machine learning and computer vision have enabled the development of fast and accurate road detectors. Commonly such systems are trained within a supervised learning paradigm where both an input sensor's data and the corresponding ground truth label must be provided. The task of generating labels is commonly carried out by human annotators and it is notoriously time consuming and expensive. In this work, it is shown that a semi-supervised approach known as co-training can provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…We use Virtual KITTI as source dataset and the original training set of KITTI-Road as target dataset. It is shown that our method outperforms all the UDA methods and one of the semi-supervised methods RGB36-super [4]. Besides, our method achieves close AP and MaxF to the fully supervised methods, further indicating the large potential of our method.…”
Section: Comparison With State-of-the-art Methodsmentioning
confidence: 64%
See 1 more Smart Citation
“…We use Virtual KITTI as source dataset and the original training set of KITTI-Road as target dataset. It is shown that our method outperforms all the UDA methods and one of the semi-supervised methods RGB36-super [4]. Besides, our method achieves close AP and MaxF to the fully supervised methods, further indicating the large potential of our method.…”
Section: Comparison With State-of-the-art Methodsmentioning
confidence: 64%
“…To overcome these issues, some methods introduce other modalities of data as supplement of information, such as Lidar [4,11,23] and depth [6,16,60,61]. Gu et al [23] progressively adapts Lidar data space into RGB data space to effectively fuse features of the two modalities.…”
Section: Related Work 21 Freespace Detectionmentioning
confidence: 99%